ANALISIS KEPUASAN PENGGUNA APLIKASI MYTELKOMSEL MENGGUNAKAN PIECES FRAMEWORK - crystanto, calvin; Abdul Munir S; Hendra Surasa (STMIK KHARISMA Makassar, 2024)
The aim of this research is to measure the level of satisfaction of MyTelkomsel application users. This research was carried out by means of analysis using the PIECES method (Performance, Information, Economy, Control, Efficiency, and Service). This research specifically surveyed 30 STMIK Kharisma Makassar students who used the MyTelkomsel application using the Google form. The calculation process will use a likes scale. The results of this research survey show that the level of satisfaction of 30 STMIK Kharisma Makassar students based on each variable is as follows: Performance 4.06 (satisfied), Information 4.17 (satisfied), Economy 4.22 (satisfied), Control and Security 3.3 (undecided), Efficiency 4.03 (satisfied), and Service 4.1 (satisfied).